Revaluing Construction in Developing Countries: A Research Agenda - Ofori, George (Penerbit Universiti Sains Malaysia, 2006)
The International Council for Research and Innovation in Building and Construction (CIB) has launched an international initiative to revalue the construction industry. This paper considers a research agenda which can be adopted to provide the framework for the revaluing of the construction industries in developing countries. It is based on a review of the literature. The paper starts by defining, “revaluing construction,” and noting its relevance to developing countries. After highlighting the importance of construction to socioeconomic development, it discusses efforts to develop the industries of developing countries. It then considers some of the features of construction and their implications to the revaluing process in developing countries. A research agenda is proposed before some recommendations are made